Refleksi Etika Bisnis Islam pada Q.S Al-jumuah Ayat 9-10 sebagai Upaya Pencegahan Fraud dalam Perspektif Akuntansi Syariah - Noviantika, Kiki Erlita; Selvia Eka Aristantia M.A (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to reflect on the Islamic business ethics values contained in QS Al-Jumu’ah verses 9–10 and their relevance in fraud prevention from the perspective of Sharia accounting. Fraudulent actions in business, such as falsifying financial reports and arranging transactions, are very dangerous issues because they undermine the economic system as a whole. This study uses a literature research method with a thematic interpretation (tafsir maudhu’i) approach to understand the meaning of Surah Al-Jumu’ah verses 9 to 10, as well as analyze scholarly works related to Sharia accounting and Islamic business ethics. The results of the study indicate that these verses provide ethical guidance that balances the obligation to worship with economic activities, so that every business transaction must be based on principles of honesty, transparency, trustworthiness, and responsibility. The integration of the values contained in the Qur’an is very important in preventing fraudulent actions because it shapes. The awareness that Allah always watches over all human actions. This study contributes theoretically by strengthening the literature on Sharia accounting based on Islamic values, and practically provides guidance for business practitioners and accountants in building a fair, honest, and integrity-driven trade system. Keywords: Sharia Accounting, QS Al-Jumu'ah Verses 9-10, Fraud, Islamic Business Ethics.